2011
DOI: 10.1111/j.1745-9125.2011.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Measures of Executive Function and Antisocial Behavior: A Meta-Analysis*

Abstract: A meta-analysis was performed to quantify the association between antisocial behavior (ASB) and performance on neuropsychological executive functioning (EF) measures. This meta-analysis built on Morgan * Additional supporting information can be found in the listing for this article in the Wiley Online Library at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
324
8
13

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(377 citation statements)
references
References 118 publications
(175 reference statements)
32
324
8
13
Order By: Relevance
“…This seems to be at odds with previous literature reviews reporting more consistent significant negative associations (also for cold EFs) in populations demonstrating antisocial and/or violent behavior (Dolan & Anderson, 2002;Morgan & Lilienfeld, 2000;Ogilvie et al, 2011; but see De Brito & Hodgins, 2009), which may be considered to represent samples with high Factor 2 scores. However, because the studies included in these reviews used a great variety of instruments to assess antisociality, they may not have captured the same aspects of Factor 2 as the measurement instruments used in the studies in the present overview.…”
Section: Working Memorycontrasting
confidence: 54%
See 2 more Smart Citations
“…This seems to be at odds with previous literature reviews reporting more consistent significant negative associations (also for cold EFs) in populations demonstrating antisocial and/or violent behavior (Dolan & Anderson, 2002;Morgan & Lilienfeld, 2000;Ogilvie et al, 2011; but see De Brito & Hodgins, 2009), which may be considered to represent samples with high Factor 2 scores. However, because the studies included in these reviews used a great variety of instruments to assess antisociality, they may not have captured the same aspects of Factor 2 as the measurement instruments used in the studies in the present overview.…”
Section: Working Memorycontrasting
confidence: 54%
“…A number of studies consistently found a negative association between antisociality and EF (e.g., see Dolan and Anderson, 2002, Morgan and Lilienfeld, 2000, and Ogilvie et al, 2011, for reviews), indirectly supporting the hypothesis that psychopathy Factor 2 is negatively associated with EF. This hypothesis fits with a recurrent finding in meta-analytic and review studies that, at least in psychopathic participants, this factor appears to be linked to prefrontal abnormalities, specifically the orbitofrontal/ventromedial prefrontal cortex, which, as indicated above, is linked to hot rather than cold EFs (e.g., Anderson and Kiehl, 2012;Gao and Raine, 2009;Yang and Raine, 2009).…”
Section: Psychopathy and Executive Functioningmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, they may do so by engaging in risky behaviors such as playing sports-an activity linked to sensation-seeking-without wearing protective gear. In doing so, they are at greater risk of damaging their frontal lobes and, thus, of losing executive function which is necessary to control one's behavior (Raine et al, 2005;Ogilvie et al, 2011). Rebellon et al's (2014) biosocial extension of Agnew's general theory of crime thus serves as an example of a synthesis between biology and sociology in the field of crime and deviance.…”
Section: Crime and Deviancementioning
confidence: 99%
“…EFs have been of particular interest because a number of studies indicate that they are malleable: family and school based interventions have both shown promise for improving EFs, particularly for children with lower initial skills (Blair and Raver 2014;Diamond and Lee 2011;Schmitt et al 2015). A large body of research has shown that EFs are consistent correlates of externalizing symptoms among both children and adults (Ogilvie et al 2011;Schoemaker et al 2013). Given the robust association between EFs and externalizing symptoms and the high societal costs of externalizing psychopathology, EFs have emerged as a promising target for prevention efforts.…”
mentioning
confidence: 99%